Stability of one difference equation with positive coefficients - Nikiforova, N. S.; Khusainov, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider a linear homogeneous difference equation of ordern with positive coefficients, which is presented in the normal form. We obtain necessary and sufficient conditions for the stability and asymptotic stability.